2023
DOI: 10.3390/vaccines11040801
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Perspective Views and Hesitancy toward COVID-19 Vaccines: A Mixed Method Study

Abstract: The worldwide uptake of COVID-19 vaccines was suboptimal throughout the pandemic; vaccine hesitancy played a principle role in low vaccine acceptance both globally and in Armenia. In order to understand the factors behind the slow vaccine uptake in Armenia, we aimed to explore the prevailing perceptions and experiences of healthcare providers and the general public related to COVID-19 vaccines. The study applied a convergent parallel mixed-methods study design (QUAL-quant) through in-depth interviews (IDI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“… 42 At the same time, researchers in other jurisdictions have also found that physicians feel pressure in staying abreast of COVID-19 evidence, 15 43 and that they are often ‘ambassadors’ of COVID-19 vaccines, but rarely given guidance on how to approach conversations with parents. 44 Moreover, studies in other countries have shown that healthcare providers have varying attitudes towards COVID-19 vaccines, 45 47 which may create dissonance when advising patients on vaccination 48 and influence their communication with patients 46 ; giving providers timely, tailored, transparent information about vaccine risks and benefits may increase their capacity to counsel patients appropriately and confidently. 4247 49 Similar to research on physicians providing COVID-19 vaccination counselling to adults 16 43 44 and parents of adolescents, 17 our findings reiterate that physicians require support in obtaining, synthesising and communicating evidence to parents of younger children to inform their vaccination decisions.…”
Section: Discussionmentioning
confidence: 99%
“… 42 At the same time, researchers in other jurisdictions have also found that physicians feel pressure in staying abreast of COVID-19 evidence, 15 43 and that they are often ‘ambassadors’ of COVID-19 vaccines, but rarely given guidance on how to approach conversations with parents. 44 Moreover, studies in other countries have shown that healthcare providers have varying attitudes towards COVID-19 vaccines, 45 47 which may create dissonance when advising patients on vaccination 48 and influence their communication with patients 46 ; giving providers timely, tailored, transparent information about vaccine risks and benefits may increase their capacity to counsel patients appropriately and confidently. 4247 49 Similar to research on physicians providing COVID-19 vaccination counselling to adults 16 43 44 and parents of adolescents, 17 our findings reiterate that physicians require support in obtaining, synthesising and communicating evidence to parents of younger children to inform their vaccination decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines vaccine hesitancy (VH) as “delay in acceptance or refusal of vaccines despite availability of vaccine services” [ 31 ]. Among other factors, vaccine hesitancy plays the principle role in low vaccine acceptance (VA) with the most common determinants being low health literacy, context-specific safety-related concerns, and mistrust [ 32 , 33 ]. Additionally, primary healthcare workers remain an important component of the taskforce to tackle VH, so, lack of training or low confidence in this group of persons will definitely reduce the potential to overcome public VH [ 9 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%